Computer Assisted Interpretation of the Profile Teleradiography - Steiner Analysis - Mihnea Iacob; Sorana Rosu; Valentina Dorobat; Irina Zetu (Romanian Dental Association for Education, 2012)
The cephalometric profile radiography represents a very important paraclinical examination in establishing the orthodontic diagnostic and treatment plan. The modern cephalometric measurements involve the use of cephalometric software. The aim of our study was to investigate, with the aid of the Orthalis cephalometric software, the malocclusion distribution in a study group, by evaluating the parameters comprised in the Steiner cephalometric analysis